A review of thin layer chromatography methods for determination of authenticity of foods and dietary supplements. Issue 10 (15th June 2018) - Sherma, Joseph; Rabel, Fred
Abstract: This paper reviews advances in qualitative and quantitative thin layer chromatography analytical methods published from 2000–2018 for assessing quality, adulteration, and authenticity of foods, beverages, and dietary supplements. Samples covered include animal and butter fats, oils, spices, flavorings, grains, honeys, soft drinks and juices, tea, sweeteners, wine and other alcoholic beverages, and vegetables, which are analyzed for a wide variety of characteristic analytes. It is suggested that TLC methods of the kind cited will continue to be used to complement the LC-MS/MS based peptide analysis methods that are being developed for food allergen detection and food fraud testing. Graphical Abstract: